Creating Ties That Bind - Freeman, R. Edward (Journal of business ethics, 2009)
The work of Donaldson and Dunfee (Ties That Bind: A Social Contracts Approach to Business Ethics, 1999) offers an example of how normative and descriptive approaches to business ethics can be integrated. We suggest that to be truly integrative, however, the theory should explore the processes by which such integration happens. We, therefore, sketch some preliminary thoughts that extend Integrative Social Contracts Theory (ISCT) by beginning to consider the process by which microsocial contracts are connected to hypernorms.